Neoliberal Globalization, Human Trafficking, and Human Security in Japan - Uddin, M. Bashir (Advances in Social Sciences Research Journal, 2020)
The issues of human trafficking and human security have been inadequately addressed in the study of political economy. How and whose human security could be assessed when considering political economy of human trafficking? This paper investigates this question, especially how contemporary globalization causes human exploitation that exacerbates human insecurity. Trafficking is a global phenomenon, the origin of which could be found in the global capitalist system. This paper examines human trafficking against the backdrop of this system that is enhanced by neoliberal globalization. While debate on prostitution, migration, criminal approach, and human rights has been at the center of anti-trafficking literature and policy initiatives in Asia, the paper argues that human trafficking is the result of human insecurity and vice versa, which could be better explained through global political economy, particularly in Japan.